2015
DOI: 10.4172/2157-7048.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Fouling and Cleaning Characteristics of Reverse Osmosis (RO) Membranes

Abstract: This work deals with fouling and successive cleaning of RO membrane fouled by an organic foulant, sodium alginate using a laboratory-scale cross flow test unit. First, spiral-wound RO membrane was fouled with sodium alginate solution up to 10% and 15%, respectively at an applied pressure of 1380 kPa with flow rate of 10 lit/min. An anionic surfactant, sodium dodecyl sulfate (SDS) was used as a chemical cleaning agent for cleaning of RO membrane. The effect of cleaning chemical dose and cross-flow velocity on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition, by analyzing the reasons, it is possible to find a suitable method for chemical cleaning of the membranes (11). Many studies have been done in details regarding the fouling reasons through which one or two reasons have been identified, however, there are less global or comprehensive studies in this regard (12)(13)(14)(15)(16)(17)(18)(19). In a study by Gutiérrez Ruiz et al, which is similar to the recent study, chemical composition and structure of fouling agents on the membrane surface were determined using the energy dispersive X-ray microanalysis and scanning electronic microscopy.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, by analyzing the reasons, it is possible to find a suitable method for chemical cleaning of the membranes (11). Many studies have been done in details regarding the fouling reasons through which one or two reasons have been identified, however, there are less global or comprehensive studies in this regard (12)(13)(14)(15)(16)(17)(18)(19). In a study by Gutiérrez Ruiz et al, which is similar to the recent study, chemical composition and structure of fouling agents on the membrane surface were determined using the energy dispersive X-ray microanalysis and scanning electronic microscopy.…”
Section: Introductionmentioning
confidence: 98%
“…The HA molecule is then solubilised and is removed with the cleaning solution (Li & Elimelech, 2004;Arijit Das et al, 2015). Arijit Das et al, (2015) observed a decrease in cleaning time from 25 minutes to 10 minutes with increase in SDS concentration from 0.1 to 0.3 mM. This was observed while cleaning a RO membrane fouled with sodium alginate (SA).…”
Section: Sodium Dodecyl Sulphate (Sds)mentioning
confidence: 99%
“…This research plans to use anionic surfactant, SDS, for membrane cleaning operations. SDS was chosen because of its popularity as a surfactant for typical membrane cleaning applications (Arijit Das et al, 2015;Beyer et al, 2010;Hijnen et al, 2012;Li & Elimelech, 2004;Li et al, 2005;Madaeni & Samieirad, 2010;Madaeni et al, 2009;Wang et al, 2018).…”
Section: Sodium Dodecyl Sulphate (Sds)mentioning
confidence: 99%
See 2 more Smart Citations